Kajian Pustaka: Gambaran Pengetahuan dan Perilaku Masyarakat untuk Mencari Fasilitas Kesehatan dalam Penanganan Penyakit Tuberkulosis - Ireneus Pape No Mbeong; Meira Erawati (Holistic Nursing and Health Science, 2021)
Introduction: The knowledge and behavior of the community in seeking health facilities for the treatment of tuberculosis were studied separately by previous researchers, so it is necessary to do a literature review to get a complete picture of this phenomenon. This study aims to obtain an overview of knowledge about tuberculosis and the behavior of people seeking health facilities in the treatment of tuberculosis in various previous studies.Methods: The study was a literature review. The sample of this study was eight articles, with inclusion criteria i.e. published in journals in the last 10 years, descriptive research, and full text. The articles were obtained through the search engines Science Direct, Scopus and Ebsco Host. The literature analysis was carried out by means of a narrative review and presented in a table.Results: The level of public knowledge about the causes of tuberculosis, signs and symptoms of the disease, modes of transmission, ways to prevent transmission, as well as knowledge that tuberculosis can be cured varied from low to high levels of knowledge. People take advantage of government and private health services, buy drugs at pharmacies, and go to traditional healers/traditional healers to get treatment for tuberculosis.Conclusion: There are still public misunderstandings about tuberculosis and obstacles in utilizing health facilities for the treatment of tuberculosis. Therefore, health education and counseling need to be improved so that public knowledge related to tuberculosis is getting better and has a positive impact on the behavior of seeking health facilities in the treatment of tuberculosis. It is necessary to conduct further studies on the factors that underlie people's behavior in seeking health facilities in the treatment of tuberculosis.